2013
DOI: 10.1016/j.econmod.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of formal and informal financial markets in quasi-emerging market economies

Abstract: The primary objective of this paper is to investigate the interaction of formal and informal …nancial markets and their impact on economic activity in quasi-emerging market economies (QEMEs). Using a four-sector dynamic stochastic general equilibrium (DSGE) model, we demonstrate that formal and informal …nancial sector loans are complementary in the aggregate, suggesting that an increase in the use of formal …nancial sector (FFS) credit creates additional productive capacity that requires more informal …nancia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
(18 reference statements)
3
14
1
Order By: Relevance
“…The implication is that increase in the cost of borrowed funds and earning assets financed by paying liabilities will negatively affects the return on asset of banks. The result is consistent with the findings of (Aruwa & Musa, 2014;Ngalawa et al, 2013) who found a negative significant relationship. Also, the asset interest yield has a positive significant impact on ROA of Nigerian banks, implying that a 1% improvement in asset interest yield, the return on asset will increase by 29%, ceteris paribus.…”
Section: Empirical Results With Roa As the Dependent Variablesupporting
confidence: 93%
“…The implication is that increase in the cost of borrowed funds and earning assets financed by paying liabilities will negatively affects the return on asset of banks. The result is consistent with the findings of (Aruwa & Musa, 2014;Ngalawa et al, 2013) who found a negative significant relationship. Also, the asset interest yield has a positive significant impact on ROA of Nigerian banks, implying that a 1% improvement in asset interest yield, the return on asset will increase by 29%, ceteris paribus.…”
Section: Empirical Results With Roa As the Dependent Variablesupporting
confidence: 93%
“…The opposing view in the literature argues that formal finance is superior to informal finance, as argued by Yang (2008), Ayyagari et al (2008), Reynolds (2011), Ngalawa and Viegi (2013), and Thai and Turkina (2013), for the following reasons:…”
Section: Discussionmentioning
confidence: 99%
“…And, it is meaningful to explore the correlation of participants' attentions in the whole private lending market in China. Recent research on the private lending market system mainly includes (1) the related research on the P2P lending market, such as borrowing success rate and default rate [14][15][16][17][18], investor behavior [19][20][21][22], and credit evaluation and market mechanism [23][24][25][26][27][28]; (2) the relationship between the informal credit market and the formal credit market [6,[29][30][31][32]; and (3) the research on offline loan [33][34][35]. erefore, this paper expands the research scope of the existing literature by investigating the extent of interdependence across time to clarify whether participants' attentions to P2P lending and offline loan are segmented or becoming more integrated.…”
Section: Introductionmentioning
confidence: 99%